Spin Dynamics and Damping in Ferromagnetic Thin Films and Nanostructures - Barman, Anjan (Springer International Publishing, 2018)
This book provides a comprehensive overview of the latest developments in the field of spin dynamics and magnetic damping. It discusses the various ways to tune damping, specifically, dynamic and static control in a ferromagnetic layer/heavy metal layer. In addition, it addresses all optical detection techniques for the investigation of modulation of damping, for example, the time-resolved magneto-optical Kerr effect technique.